Masculinity in Islam: Exploring the Dynamic Shift in Gender Roles in A Postmodern Context - Rao, Kashaf Shafique; Jamil, Nabiha (South Asian Journal of Religion and Philosophy (SAJRP), 2023)
This research investigates the evolving gender roles in the light of Islam, focusing on the understudied and much-neglected concept of masculinity in the context of postmodernism. Masculinity in Islam refers to men being the sole providers, breadwinners, and protectors of the family, whereas postmodernism acknowledges diverse and malleable expressions of masculinity. This study employs a multi-dimensional approach, analysing Islamic scriptures, historical perspectives, and ongoing discourse on gender roles, guided by postmodern principles and Islamic beliefs. It analyses whether Islam accommodates reinterpreted, newly constructed concepts of masculinity within postmodern discourses and how Muslim men should navigate tensions between traditional Islamic roles assigned to them and new approaches. Additionally, it delves into the influence of contemporary societal changes on shaping modern Islamic masculinity. By doing so, this study makes a valuable contribution to the wider discourse on gender, particularly masculinity, in Islam under the postmodern lens. The significance of these findings lies in their potential to promote intercultural dialogue, challenge stereotypes, and foster gender equity within Muslim communities.